2014
DOI: 10.1039/c4fo00438h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of broccoli phytochemical extract on release of fatty acids from salmon muscle and salmon oil during in vitro digestion

Abstract: The aim of the present work was to study the effect of a broccoli phytochemical extract (Br-ex) on the release of fatty acids (FA) from salmon muscle (SM) and salmon oil (SO) during in vitro digestion. The hypothesis of the study was that Br-ex contains polyphenols which might act as pancreatic lipase inhibitors. The effect on the release of specific FA, in particular the long-chain n-3 polyunsaturated fatty acids (PUFAs), EPA (C20:5 n-3) and DHA (C22:6 n-3), was recorded, and the impact of the SM matrix was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Further, the ingestion route and whether or not PUFA are accompanied by phytocomponents such as broccoli [37], alternates the effective DHA/EPA concentrations in-vivo. Finally, genetic variations [22] and related geneediet interactions enlarge the array of individual diversity in biological effects in-vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the ingestion route and whether or not PUFA are accompanied by phytocomponents such as broccoli [37], alternates the effective DHA/EPA concentrations in-vivo. Finally, genetic variations [22] and related geneediet interactions enlarge the array of individual diversity in biological effects in-vivo.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the bioaccessibility of specific FAs could be affected by the food matrix and fatty acid position on the TAG [23,24]. Therefore, methods capable of providing FA-specific bioaccessibility information at certain extents of lipolysis are desired.…”
Section: Introductionmentioning
confidence: 99%